Pengaruh Kualitas, Harga, Promosi Terhadap Keputusan Pembelian Pada Kedai Kopi Janji Jiwa Di Purwodadi - Dina Damayanti; Edy Purwo Saputro (POLITEKNIK LP3I JAKARTA, 2023)
The purpose of this study was to examine how product price, quality, and promotion affect customer decisions to buy at the Promise Soul coffee shop in Purwodadi. Associative research is this type of research. This research uses quantitative methodology. Demographics and samples in this study are customers who have purchased products from the Janji Jiwa Purwodadi coffee shop and have met the requirements. The number of samples for this study were 100 respondents. Primary data is the data source for this research. In this study, a 5-point Likert scale was used as a scoring system. Data analysis using SPSS version 22. According to the findings of the analysis, product quality has no positive or substantial influence on purchase choice, but product price has a positive and substantial influence on purchase choice. Price has a positive and significant influence on purchasing choice.Keywords: Product Quality, Product Price, Promotion, Purchase Decision